Management control systems - Anthony, Robert N. (Robert Newton), 1916-2006.; Govindarajan, Vijay (Boston : McGraw-Hill/Irwin, 2007)
Helps students to develop the insight and analytical skills required of managers in contemporary times. This edition shows students how real-world managers design, implement, and use planning and control systems to implement business strategies. It aims to offer a diversity of cases that are balanced with content and research.
Includes bibliographical references and indexes.
Keywords: Industrial management; Industrial management -- Case studies; Kostenkontrolle